2013
DOI: 10.4082/kjfm.2013.34.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Blood Pressure Measurements Obtained Using an Automatic Oscillometric Sphygmomanometer Depending on Clothes-Wearing Status

Abstract: BackgroundAccording to the current guidelines for blood pressure monitoring, clinicians are recommended to measure blood pressure by completely exposing the upper arm. However, it is a common practice that blood pressure is measured with the cuff placed over the sleeve or with the sleeve rolled up. We therefore conducted this study to examine whether there are any differences in blood pressure measurements among the three different settings: the sleeve group, the rolled sleeve group, and the bare arm group.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…No statistical differences were determined between SBP/DBP measurements taken over the sleeve and below a rolled-up sleeve. These data are supported by the findings of previous studies 7,9-12…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…No statistical differences were determined between SBP/DBP measurements taken over the sleeve and below a rolled-up sleeve. These data are supported by the findings of previous studies 7,9-12…”
Section: Discussionsupporting
confidence: 92%
“…In those studies, the BP of each patient was measured three times: over a sleeve, below a rolled-up sleeve, and on a bare arm. The clothing thickness of the vast majority of patients (83.7%) was < 2 mm7 and the mean clothing thickness was 1.7 mm10. Neither study reported statistically significant differences among the three BP measurements.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations